How to lose your ass and regain your life : reluctant confessions of a big-butted star - Alley, Kirstie ([Emmaus Pa.] : Rodale, 2005)
In a humorous memoir, the actress explores the American obsession with food, fat, sex, love, beauty, and weight as she recounts her own battle with the bulge and reflects on what it means to be overweight in a skinny-obsessed world
Little suede pants -- Lillian's diet -- Cocaine and Dianetics -- Lies, a trilogy -- What does baby want? -- Lies, a trilogy -- Lies, a trilogy -- Lilliput -- Divine attention -- Mamsley -- Farewell to Lillian -- Sky class - - Go hemp yourself! -- Driving Miss Kirstie -- The two faces of fat -- "C.W." -- Cocktail attire -- Two faces of fat -- Lord Jim -- Pooping.
Keywords: Alley, Kirstie; Actors -- United States -- Biography; Obesity. -- Biography